Agronomic performance of common and tepary bean genotypes and their response to ashy stem blight in Isabela and Lajas, Puerto Rico. Issue 2 (27th July 2021) - Viteri, Diego M.; Linares, Angela M.
Abstract: The seed yield potential of Phaseolus genotypes varies according their genetic background, environmental conditions, agronomic management, presence of pathogens, and/or their interactions. We evaluated the agronomic performance of 27 common bean ( Phaseolus vulgaris L.) and three tepary bean ( P. acutifolius A. Gray) genotypes and their response to ashy stem blight (ASB) caused by Macrophomina phaseolina (Tassi) Goidanich. The 30 bean genotypes were planted in Isabela and Lajas, Puerto Rico, during 2019–2020. Tepary bean PI 313488 had the higher mean seed yield values (1, 077–1, 080 kg ha −1 ), compared with PI 462025 and PI 477037 (187–605 kg ha −1 ), in Isabela and Lajas on October 2019. Likewise, 92BG‐7, SB‐DT1, SEN 21, SER 16, SER 22, TARS‐MST1, and XAN 176 common bean genotypes had the highest yield in Isabela (>1, 300 kg ha −1 ) and Lajas (>1, 000 kg ha −1 ) on February 2020. Conversely, 92BG‐7, 'Bella', 'Jaguar', 'Matterhorn', SB‐DT1, SEN 3, SEA, and SER breeding lines, 'Tio Canela 75', 'UI 320', USPT‐WM‐1, VA 19, 'Verano', and XAN 176 had the lowest seed yield (<150 kg ha −1 ) compared with PI 313488, PI 462025, PI 477037, and TARS‐MST1 (345–511 kg ha −1 ) in Lajas on May 2019. Moreover, higher ASB incidence (47.6–66.3%) and severity (scores of 5.3–5.8) were observed in Lajas than Isabela (36.6–50.0% and 3.6–4.2, respectively). PI 313488 had lower ASB severity (≤4) in both locations, whereas 'Bill‐Z' and 'Matterhorn' were susceptible (>7) in Lajas. Prolonged periods of high temperatures (27.0–30.6°C) at night during reproductive stages apparently affected the seed yield and increased the ASB incidence/severity in Lajas.